2019
DOI: 10.1074/jbc.ra119.011350
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free transcription in Xenopus egg extract

Abstract: Edited by John M. Denu Soluble extracts prepared from Xenopus eggs have been used extensively to study various aspects of cellular and developmental biology. During early egg development, transcription of the zygotic genome is suppressed. As a result, traditional extracts derived from unfertilized and early stage eggs possess little or no intrinsic transcriptional activity. In this study, we show that Xenopus nucleoplasmic extract (NPE) supports robust transcription of a chromatinized plasmid substrate. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 61 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…In the embryos of rapidly developing species, transcription activity is regulated by the density of maternally-supplied histones ( 39 , 40 ). We previously showed that a similar mechanism also controls transcription in NPE ( 26 ), which supports nucleosome formation ( Supplementary Figure S3A ) ( 41 ). To test whether BRCA1’s ability to suppress transcription was linked to histone density, we compared transcription in mock- and BRCA1-depleted extracts incubated with 2.5 ng/ul pActin and increasing concentrations of a ‘carrier’ plasmid with no sequence homology.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In the embryos of rapidly developing species, transcription activity is regulated by the density of maternally-supplied histones ( 39 , 40 ). We previously showed that a similar mechanism also controls transcription in NPE ( 26 ), which supports nucleosome formation ( Supplementary Figure S3A ) ( 41 ). To test whether BRCA1’s ability to suppress transcription was linked to histone density, we compared transcription in mock- and BRCA1-depleted extracts incubated with 2.5 ng/ul pActin and increasing concentrations of a ‘carrier’ plasmid with no sequence homology.…”
Section: Resultssupporting
confidence: 65%
“…Despite extensive study, the context and functional role that BRCA1 plays in transcription regulation remains poorly understood. We recently showed that nucleoplasmic extract (NPE) readily promotes transcription of plasmid-borne gene constructs ( 26 ), unlike traditional egg extracts where transcription is suppressed ( 27 ). Using the NPE system, we sought to investigate BRCA1’s role as a transcription regulator.…”
Section: Introductionmentioning
confidence: 99%
“…Equally, reconstitution involves purification of multiple proteins and fine-tuning of reaction conditions, whilst extracts contain a complete complement of proteins required for the reactions discussed here, including previously uncharacterised proteins. This justifies development of new single-molecule approaches in extracts to give a detailed insight into pathways like non-NHEJ DNA repair mechanisms and transcription [50]. Further study of the intersection between chromosome replication, repair and organisation in egg extracts will be interesting [26,33].…”
Section: Resultsmentioning
confidence: 99%
“…This article is a US Government work. It is not subject to copyright under 17 USC The copyright holder for this preprint this version posted November 7, 2021. ; https://doi.org/10.1101/2021.11.06.467569 doi: bioRxiv preprint 2015; Barrows and Long, 2019). Interestingly, in vitro chromatid reconstitution in this system specifically requires the use of an egg-specific histone (Shintomi et al, 2015;Shechter et al, 2009), histone H2A.X-F (also known as H2A.X.3), and it was suggested that this variant is a better substrate of the FACT complex chaperone than is the canonical histone H2A, which is also present in egg extracts (Shintomi et al, 2015;Wang et al, 2014).…”
Section: Roles Of the Tfiih Complex In Chromosome Condensationmentioning
confidence: 99%
“…To examine possible relationships between transcription-associated activities and mitotic chromosome condensation, we used cell-free Xenopus M phase egg extracts, a system in which condensin function is well characterized and general transcription is silenced (Kinoshita et al, 2015;Hirano and Mitchison, 1994;Barrows and Long, 2019;Chen et al, 2019;Amodeo et al, 2015). As previously demonstrated (Hirano and Mitchison, 1993;Shintomi et al, 2015), sperm nuclei incubated with a high-speed supernatant (HSS) of egg extracts first swell during the exchange of protamines for maternal histones, assemble into a diffuse "cloud" of chromatin, and gradually form clusters of condensed single-chromatid structures (Figure 1A).…”
Section: The Tfiih Complex Is Required For Chromosome Condensation In Xenopus Egg Extractsmentioning
confidence: 99%